Rhabdomyosarcoma of the sternum: Resection and reconstruction - Mohammed Babiker; Mohammad Al-Onazi; Khaleel AlBatniji; Ahmad Jawad AlHendi; Ayman Ahmed; Mohammed Saleh; Amani Alansari; Mohammed ElMahmoud (Elsevier, 2020)
Chest wall tumors either benign or malignant are rare in children. Primary chest wall tumors accounts for less than 2% of the primary body tumors in children. In many of these tumors wide local surgical excision is the only modality of the oncological management. We report a 2 year old child as the youngest patient with rhabdomyosarcoma arising from anterior chest wall muscles that involves the sternum, as well as, the surgical resection and the choice of surgical technique for reconstruction of the anterior chest wall defect at this age.